Astragaloside IV ameliorates radiation-induced senescence via antioxidative mechanism. (15th May 2020) - Liu, Xin; Shang, Shuying; Chu, Weiwei; Ma, Liang; Jiang, Chenxin; Ding, Yanping; Wang, Jianlin; Zhang, Shengxiang; Shao, Baoping
Abstract: Objectives: Ageing is a universal and gradual process of organ deterioration. Radiation induces oxidative stress in cells, which leads to genetic damage and affects cell growth, differentiation and senescence. Astragaloside (AS)-IV has antioxidative, anti-apoptotic and anti-inflammatory properties. Methods: To study the protective mechanism of AS-IV on radiation-induced brain cell senescence, we constructed a radiation-induced brain cell ageing model, using biochemical indicators, senescence-associated galactosidase (SA-β-gal) senescence staining, flow cytometry and Western blotting to analyse the AS-IV resistance mechanism to radiation-induced brain cell senescence. Key findings: Radiation reduced superoxide dismutase (SOD) activity and expressions of cyclin-dependent kinase (CDK2), CDK4, cyclin E and transcription factor E2F1 proteins, and increased expressions of p21, p16, cyclin D and retinoblastoma (RB) proteins, malondialdehyde (MDA) activity, SA-β-gal–positive cells and cells stagnating in G1 phase. After treatment with AS-IV, the level of oxidative stress in cells significantly decreased and expression of proteins related to the cell cycle and ageing significantly changed. In addition, SA-β-gal–positive cells and cells arrested in G1 phase were significantly reduced. Conclusions: These data suggest that AS-IV can antagonize radiation-induced brain cells senescence; and its mechanism may be related to p53-p21 and p16-RB signalling pathways of ageing regulation.